How do older adults experience intergenerational relationships? Different cultures, ambivalent feelings. Issue 8 (3rd August 2018) - von Humboldt, Sofia; Monteiro, Ana; Leal, Isabel
ABSTRACT: Objective : Intergenerational relationships are central for older adults' well-being. In spite of the reiterated value of intergenerational interactions between older adults and grandchildren, there is paucity of research that has analyzed these relationships at a cross-national level. The current study purports to analyze how older adults conceptualize intergenerational relationships. Method : In this qualitative study, in-depth interviews were conducted with 316 older adults, aged 65–102, currently living at home representing three different nationalities. Verbatim transcripts were examined. Results : Data analysis generated six themes representing intergenerational relationships: affection and reward; interest and integration; quality of grandparent–grandchild interaction; definitions of privacy and boundaries; provision of support; and obligations regarding childcare, supportive, and conflictual. Conclusions : The empirical findings indicated older adults' ambivalence over intergenerational relationships and contradictory expectations of support from grandchildren.